A case report of arrhythmogenic ventricular cardiomyopathy presenting with sustained ventricular tachycardia arising from the right and the left ventricles before structural changes are documented. Issue 1 (25th January 2020) - Belhassen, Bernard; Shmilovich, Haim; Nof, Eyal; Milman, Anat
Abstract: Background: Arrhythmogenic ventricular cardiomyopathy (AC) is a genetic progressive disease characterized by fibro-fatty replacement of either ventricles in isolation or in combination. Arrhythmogenic ventricular cardiomyopathy is frequently associated with ventricular tachycardia (VT) having a left bundle branch block (LBBB) morphology and much more rarely with VT having right bundle branch block (RBBB) morphology even when the left ventricle is involved. Cardiac magnetic resonance (CMR) imaging plays a key role in the diagnosis of AC. Sustained VT in AC may occur in the concealed stage of the disease before the manifestation of morphological abnormalities on echocardiogram; however, they almost always are accompanied by structural abnormalities of the ventricles on CMR. Case summary: A 54-year-old man presented with sustained VT of LBBB configuration consistent with the diagnosis of AC but with no right ventricular (RV) anomalies at repeat CMR. Ten years later, he developed sustained VT with RBBB morphology and structural changes at CMR compatible with RV involvement in the setting of AC. Two years later, he suffered from recurrent identical sustained RBBB-VT with typical CMR signs of left ventricular involvement. Genetic analysis was negative for any known mutation. Discussion: In the present report, we describe a patient with AC who first exhibited LBBB- and 10 years later RBBB-sustained VT. Contrasting with what is usually observed in patients with AC, documentations of the VT's arising from either ventricle were found to precede the structural anomalies in the respective cardiac chambers. This case highlights that normal CMR does not exclude underlying AC contrary to the perceptions of many clinicians. In addition, it strongly encourages repeating CMR after 1–2 years when the diagnosis of AC is highly suspected.